HTERT gene expression levels and telomerase activity in drug resistant MCF-7 cells - Sakin, V.; Eskiocak, U.; Kars, M.D.; Iseri, Ö.D.; Gunduz, U. (Experimental Oncology, 2008)
Cancer cells and some highly proliferative normal cells can stabilize telomere lengths by telomerase, which adds hexameric repeats to the ends of linear chromosomes. In this study, the activity of telomerase reverse transcriptase (hTERT) and its gene expression levels were investigated in paclitaxel, docetaxel, vincristine and doxorubicin resistant human MCF-7 breast adenocarcinoma cells. Materials and Methods: Resistant cell lines were developed by stepwise selection of cells (MCF-7/S) in increasing doses of paclitaxel (MCF-7/Pac), docetaxel (MCF-7/Doc), vincristine (MCF-7/Vinc) and doxorubicin (MCF-7/Dox). Antiproliferative effects of anticancer drugs were evaluated by XTT assay and IC50 values for different drugs were determined from cell proliferation curves. Expression levels of hTERT gene in sensitive and resistant cells were analyzed by RT-PCR. TRAP-Silver Staining assay was used to evaluate telomerase activities in these cells. Results: When drug resistant and sensitive MCF-7 cells were compared no significant differences were observed in hTERT expression levels and telomerase enzyme activities. Conclusion: This report demonstrates that drug resistance developed against paclitaxel, docetaxel, vincristine and doxorubicin in MCF-7 cells is independent of the expression of hTERT gene and telomerase activity. В опухолевых клетках, а также некоторых нормальных клетках с высоким пролиферативным потенциалом длина теломеров может стабилизироваться за счет фермента теломеразы, добавляющего гексамерные повторы к концам линейных хромосом. Цель: проанализировать активность обратной транскриптазы теломеразного комплекса и экспрессию гена теломеразы в клетках MCF-7 аденокарциномы молочной железы человека, устойчивых к паклитакселу, доцетакселу, винкристину и доксорубицину. Материалы и методы: сублинии клеток MCF-7, обладающих лекарственной резистентностью, были полу- MCF-7, обладающих лекарственной резистентностью, были полу -7, обладающих лекарственной резистентностью, были получены путем селекции исходных клеток при культивировании их в присутствии возрастающих доз паклитаксела (MCF-7/Pac), доцетаксела (MCF-7/Doc), винкристина (MCF-7/Vinc) и доксорубицина (MCF-7/Dox). Антипролиферативный эффект противоопухолевых препаратов определяли в ХТТ-тесте. Величины IC50 для различных препаратов определяли по кривым пролиферации клеток. Уровень экспрессии гена hTERT в чувствительных и резистентных клетках анализировали методом ОТ-ПЦР. Теломеразную активность определяли с помощью набора TRAPeze. Результаты: проанализированные резистентные линии клеток MCF-7 не отличались от исходной линии ни по уровню экспрессии гена hTERT, ни по уровню теломеразной активности. Выводы: развитие лекарственной резистентности к паклитакселу, доцетакселу, винкристину и доксорубицину в клетках MCF-7 не связано с изменениями экпрессии гена hTERT или уровня теломеразной активности в них.